ANALISIS PENGARUH KUALITAS LAYANAN, PERSEPSI HARGA DAN NILAI PELANGGAN TERHADAP KEPUASAN PELANGGAN (Studi Kasus pada Hotel Bahari Inn Tegal) - Ryan Ardian Prasojo Mahardika, 10.05.51.0103; Widyasari, Suzy (Students Journal of Economic and Management, 2014)
This study entitled the effect of service quality, perception price, customer value to customer satisfaction aimed to analyze customer satisfaction in Bahari Inn Hotel Tegal. The population in this study was customers staying in Bahari Inn Hotel Tegal. Sampling method used in this study was âpurposive samplingâthat technique determines the sample with particular consideration in accordance with the desired destination with the number of samples taken 95 people. The collected data were analyze using factor analysis to test the validity of the statement items, cronbach alpha of each partial independent variables were tested with the coefficient of determination and test fit the model to test and prove the influence of the partial each independent variable. The results of this study indicated that service quality, price perception, and customers value had a significant positive effect on customer satisfaction in Bahari Inn Hotel Tegal. The variable which most affected customer satisfaction was service quality then followed with customer value and price perception.Keyword: Service quality, Price Perception, Customer Value , Customer Satisfaction